IET Seminar Digests 2008
DOI: 10.1049/ic.2008.0694
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of CP-OFDM with IOTA-OFDM under typical system imperfections

Abstract: Abstract-In this paper we compare the performance of OFDM with a cyclic prefix (CP) and isotropic orthogonal transform algorithm (IOTA) OFDM without cyclic prefix under typical system imperfections such as channel estimation errors and frequency offset. The IOTA-OFDM system is based on offset quadrature amplitude modulation (OQAM) and promises an increased immunity to both inter-carrier interference (ICI) and inter-symbol interference (lSI). Moreover, IOTA-OFDM does not require a CP which makes it spectrally m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…A limitation of the paper was that it was implemented in an uncoded OFDM system [4]. Although a comparison of cyclic prefix (CP)-OFDM with OFDM-IOTA under a typical system was proposed, the disadvantage of the system was the existence of frequency offset error at the receiver [5]. A hardware architecture of the pulse shaping filter used in multicarrier systems was proposed in [6].…”
Section: Related Workmentioning
confidence: 99%
“…A limitation of the paper was that it was implemented in an uncoded OFDM system [4]. Although a comparison of cyclic prefix (CP)-OFDM with OFDM-IOTA under a typical system was proposed, the disadvantage of the system was the existence of frequency offset error at the receiver [5]. A hardware architecture of the pulse shaping filter used in multicarrier systems was proposed in [6].…”
Section: Related Workmentioning
confidence: 99%
“…For FBMC, among different prototype filters, such as half‐cosine, root‐raised‐cosine, isotropic orthogonal transform algorithm (IOTA), extended Gaussian function (EGF), etc., the localisation property is optimal with the IOTA function which has the same shape in time and frequency domains. Having some level of ISI (due to channel dispersion) and ICI when the channel is time varying is a common problem in multicarrier systems, however it is shown that OFDM/OQAM with IOTA pulse shaping is more resistant to these interferences [6–10]. OFDM/OQAM systems provide orthogonality in the real domain, therefore, instead of using complex baseband symbols in OFDM/QAM scheme, real valued symbols modulated by offset QAM are transmitted on each subcarrier [11].…”
Section: Introductionmentioning
confidence: 99%
“…OFDM/OQAM systems provide orthogonality in the real domain, therefore, instead of using complex baseband symbols as in OFDM/QAM scheme, real valued symbols modulated by offset QAM are transmitted on each sub-carrier [5]. OFDM/OQAM systems and conventional OFDM systems in a realistic mobile communication context (in both time and frequency dispersive channels) have been compared in [10], [11], [12] where it was shown that the performance advantage of OFDM/OQAM with IOTA pulse shaping over conventional OFDM can be up to 4.5 dB depending on different types of wireless propagation channels.…”
Section: Introductionmentioning
confidence: 99%